Entrapment of Embolic Protection Device within Peripheral Stent: Troubleshooting When Novelty Fails - Arunachalam, Venkat; Valakkada, Jineesh; Ayyappan, Anoop; Kannath, Santhosh (Journal of Clinical Interventional Radiology ISVIR, 2024)
The use of embolic protection devices (EPD) in peripheral vascular procedures with higher risk of distal embolic shower has gained wider acceptance with evidence mounting in favor of its use. We report our unique experience on the circumstances leading to and management of entrapment of an EPD within peripheral stent during management of a patient with critical limb ischemia.
Keywords: filter entrapment; retrieval; embolic protection devices